Repurposing bortezomib for choroidal neovascularization treatment via antagonizing VEGF-A and PDGF-D mediated signaling. (March 2021) - Liu, Yimei; Feng, Meiling; Cai, Jingjing; Li, Shifeng; Dai, Xufeng; Shan, Ge; Wu, Shengzhou
Abstract: Neovascular age-related macular degeneration (neoAMD) is the leading cause of blindness in AMD and manifests as choroidal neovascularization (CNV). Anti-vascular endothelial growth factor (VEGF) therapies are the mainstay treatments but with limited efficacy and cause detrimental effects on the retina after long-term application. These disadvantages warrant alternative strategy. Herein, we examined the effect on CNV by intravitreal injection of bortezomib, a reversible proteasome inhibitor, and further dissected the mechanism. Krypton red Laser was used to create CNV model in mice. The angiogenesis volume was assessed in choroidal flat-mount with isolectin GS-IB4 labeling and the leakage was examined with fluorescein fundus angiography. Injection of Borsub inhibited angiogenesis in the CNV model which was dose-dependent; the injection significantly inhibited leakage as well. Furthermore, Borsub injection reduced the contents of VEGF-A, macrophage chemotactic factor 1 (MCP-1), and platelet-derived growth factor (PDGF)-D but not PDGF-B, examined by enzyme-linked immunosorbent assay, in choroid/retinal pigment epithelium (RPE) tissue. These injections also reduced phospho-VEGFR-2 and phospho-PDGFRβ in choroid/RPE tissue examined by immunoblotting. Moreover, Borsub inhibited the recruitment of mural cells or macrophages to laser-injured spots. Injection of Borsub indicated negative effect on scotopic and photopic responses recorded by electroretinogram. Altogether, intravitreal injection of Borsub significantly reduced CNV by antagonizing VEGF-A/Flk-1 and PDGF-D/PDGFRβ pathways without impacting electroretinography parameters. Thus, Borsub may offer an invaluable therapy for the prevention and treatment of neoAMD. Highlights: Intravitreal injection of bortezomib significantly reduced CNV. Injection of bortezomib blocked VEGF-A and PDGF-D-mediated signaling. Injection of bortezomib did not impact electroretinography parameters.